A Practical Explication of the Knowledge Rule of Informative Speech Acts. (19th September 2011) - Kelp, Christoph
<x xml:space="preserve">Abstract</x> Abstract: This paper defends the knowledge rule of informative speech acts. It is argued that Edward Craig's insightful practical explication of the concept of knowledge can be extended to motivate the knowledge rule. A number of problem cases for the knowledge rule are addressed and accommodated.